2009
DOI: 10.1007/s12088-009-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and biotechnological potential of Paenibacillus polymyxa: a minireview

Abstract: Microbial diversity is a major resource for biotechnological products and processes. Bacteria are the most dominant group of this diversity which produce a wide range of products of industrial signifi cance. Paenibacillus polymyxa (formerly Bacillus polymyxa), a non pathogenic and endospore-forming Bacillus, is one of the most industrially signifi cant facultative anaerobic bacterium. It occurs naturally in soil, rhizosphere and roots of crop plants and in marine sediments. During the last two decades, there h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
135
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(141 citation statements)
references
References 86 publications
1
135
0
5
Order By: Relevance
“…Besides mineral fertilization, biofertilizers such as atmospheric N fixing rhizobacteria (Fuentes-Ramirez et al 2006) may offer an interesting environmental alternative. They seem to improve plant productivity (Lal and Tabacchioni 2009), favor C sequestration (Sohi et al 2010), and require little energy for their production or for their application since they are usually applied by seed inoculation. Their use does not release as much GHG as N fertilizers and they do not pollute surface waters.…”
mentioning
confidence: 99%
“…Besides mineral fertilization, biofertilizers such as atmospheric N fixing rhizobacteria (Fuentes-Ramirez et al 2006) may offer an interesting environmental alternative. They seem to improve plant productivity (Lal and Tabacchioni 2009), favor C sequestration (Sohi et al 2010), and require little energy for their production or for their application since they are usually applied by seed inoculation. Their use does not release as much GHG as N fertilizers and they do not pollute surface waters.…”
mentioning
confidence: 99%
“…These increments in dry weight may be associated with direct mechanisms for the production of growth hormones (gibberellins, auxins), increased availability of iron and/or indirect effects as biocontrol, antibiotic production and competition for nutrients, as reported by Lal & Tabacchioni (2009). Moura et al (2007) working with fertilization of melon found no difference (p < 0.05) among treatments, but there was a better result for the biofertilizer at the highest level (BP200) and the mixture of rocks (RP + RK) in double the recommended dose for chemical fertilizer plus sulfur.…”
Section: Resultsmentioning
confidence: 92%
“…(A) Dry matter production of shoots of cowpea bean in relation to fertilization; (B) N content in shoots of cowpea bean in the studied treatments mechanisms in use (Lal & Tabacchioni, 2009) for absorption of minerals timely harvest of cowpea bean. This implies that the improvement of this process also requires an evaluation of the adequacy of the best time of hatching biofertilizer added to the soil and the incubation conditions.…”
Section: Bmentioning
confidence: 99%
“…On the other hand, Paenibacillus species are some of the most industrially significant facultative anaerobic bacteria. Their natural habitat includes the soil, the rhizosphere and the roots of crop plants, and marine sediments [29]. Although we have limited knowledge about their genomic information, the academic interest towards their ecological and biotechnological roles has increased in the last 20 years or so.…”
Section: Staphylococcus Saprophyticusmentioning
confidence: 99%
“…For example, P. polymyxa has a lot of different features like nitrogen fixation, promotion of plant growth, solubilization of phosphorus, production of exopolysaccharides, hydrolytic enzymes, antibiotics, cytokinins and other valuable and useful compounds, such as optically active 2,3-butanediol. Other Paenibacillus strains boost the flocculation and enhance the soil porosity [29].…”
Section: Staphylococcus Saprophyticusmentioning
confidence: 99%